Behavioral Drivers of First-Time Blood Donor Retention in Yogyakarta, Indonesia - Mohammad Adam Jerusalem; Kartika Ratna Pertiwi; Agung Wijaya Subiantoro; Ummi Fakhriyah Jayatri; Dyantika Putry Mahmud (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
ntroduction: Voluntary blood donor retention is still challenging in blood stock issue, specifically in decentralization system like in Indonesia. Most of previous research has focused on logistic or survey-based study, hence it cannot explain the dynamics of actual donor behavior from time to time. Further, there is a lack of understanding of donor retention as a behavioral process that develops longitudinally. This research aims to identify the first-time donor retention pattern and also demographic characteristics and relevant service context as basis for developing more effective health promotion strategies. Methods: This research implemented a retrospective longitudinal cohort design based on routine blood donor registration data of 26,170 first-time donors from five Blood Transfusion Units in the Province of Special Region of Yogyakarta during the period 2021–2024. Donor visit trajectories were analyzed using a sequence analysis approach with the optimal matching method and then grouped using the Partition Around Medoids algorithm. Cluster validity was determined using the silhouette and Dunn indeces and further analyzed descriptively and statistically to examine differences in characteristics among groups. Results: The study found three main donor patterns, i.e. one-time donors, regular donors, and donors who have temporarily stopped donating. City of Yogyakarta has highest retention rate, while Gunung Kidul is dominated by donors-once. Male donors tend to dominant among regular donors, on the contrary female donors are more represented in temporarily stopped donating. The vital finding points out the first 6–12 months engagement after initial donation is strongly associated with donor behavioral intentions. Conclusion: Blood donor retention is dynamic process that is influenced by demographic characteristics and service context. A limitation of this study is the lack of consideration of psychosocial as a variable. However, the use of actual longitudinal data is a major strength of this study. The managerial implication of this study is that segmentation-based strategies, strengthening interventions in the early phase, and gender-sensitive and community-based approaches are needed to increase donor retention in a sustainable manner.